KATEGORI DAN EKSPRESI LINGUISTIK DALAM BAHASA JAWA SEBAGAI CERMIN KEARIFAN LOKAL PENUTURNYA: KAJIAN ETNOLINGUISTIK PADA MASYARAKAT PETANI DAN NELAYAN - Fernandez, Inyo Yos (Kajian Linguistik dan Sastra, 2008)
The study examines the local discernment of Javanese community in Central Java, DIY, and in East Java, viewed from the work of farmer and fisher which is reflected in their expression and linguistic category of Javanese language. The samples of the study are farmers in the village Wonosari (on the hill of Gunung Kawi, Malang, East Java), Â Kemuning Sari (Jember, East Java), Petung Kriyana (Pekalongan, Central Java), fishers of the south coast in the village Puger (Jember, East Java) and those in the village Kemadang (Gunung Kidul, DIY). The data were collected by using eth- nography and ethno-science methods in the framework of ethno-linguistics. The study shows that based on the Javanese linguistic expression and category, there is a myth of the Javanese farmers represented in the ritual ceremony of rice pre-plantation as the reflection of thank to god âDewi Sriâ. The myth is still contained within the register âwiwitanâ as managed by the leader of ceremony. So, there is an enclosed Javanese life style within to care to vertical and horizontal human relation in nature. Such phenomena also occur in the Javanese fishers in the south coast, i.e. in their local understanding to keep the natural force which may sometimes threaten their safety when working on the sea or when they have to meet the natural symbol âNyi Rara Kidulâ. Among the related registers to use are âlabuhan kapatâ âthanksgiv- ingâ, and âselametan petik lautâ (every the Syura month 15th). This reflects the Javanese life styleâs care to the natural, social, and thought ecology. The Javanese worth culture asset represents the local discern crystallization which has been en- closed within the Javanese linguistic expressions and categories.Â Key words:Â Â  Â local discernment, ranah bahasa petani dan nelayan, ethno-linguistics, ethno-science, dan ecology.Â